THE INTEGRATION OF PUMPED STORAGE STATIONS IN THE BRAZILIAN NATIONAL INTEGRATED SYSTEM: ELECTRICAL SYSTEM BEHAVIOUR ANALYSIS - Koutnik, Jiri; Zoby, Maria R. G.; Gonçalves, Manuel N. F.; Lopes, Rafael A. (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
The increasing share of renewable sources of energy introduces new issues in terms of system operation and equipment design. The insertion of pumped storage stations in an existing electrical system has been previously observed worldwide. In Brazil, the combination of various favourable conditions stimulates the installation of pumped storage stations. In the analysis for the implementation of these stations it is fundamental the correct simulation of the electrical system operating conditions. The unstable behaviour of renewable and non dispatchable sources, the behaviour of pumped storage stations, and their contribution to optimization of power system operating conditions must be well modelled and investigated. Computational simulations are a cheap and accurate tool. The current work presents two real cases of operation simulations of pumped storage stations. One presents grid stability investigations and the other concerns computational simulations of back-to-back operation of a power plant. The first study gives an overview of investigations conducted for a variable speed project Frades II showing what impact requirements have on the unit and converter design. The back-to-back start procedure is performed according to the constraints imposed by the rated current on the starting circuit. Current and power during system acceleration are kept under acceptable levels.